2016
DOI: 10.1002/asia.201600543
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Preferences and the Phase Stability of Fullerene Hexa‐adducts

Abstract: Molecular conformation and the assembly structure determine the spatial arrangements of the constituent units and the functions of a molecule. Although, fullerene hexa-adducts (FHAs) have been known as functional materials with great versatility, their conformational preferences and phase stability remain a complicate issue. By choosing bithiophene (T2 ) and dodecyl bithiophene (C12 T2 ) as the peripheral units of FHA, and using microscopic, scattering and diffraction characterizations, our study reveals how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In supramolecular chemistry, it is important to let the structural factors imbedded at the molecular level be transferred up to the higher hierarchical levels. To connect the shapeshifting between the molecular and supramolecular levels, herein, we incorporated the conformational flexibility of star molecules , into the design of giant molecules to develop a shapeshifting molecule that accesses the Ostwald’s stages of nucleation. The design principle was inspired first by Saez and Goodby, who have demonstrated that the gross shapes of star-like molecules can be adjusted by chemically modifying the density and attachment orientation of the peripheral mesogenic groups .…”
Section: Introductionmentioning
confidence: 99%
“…In supramolecular chemistry, it is important to let the structural factors imbedded at the molecular level be transferred up to the higher hierarchical levels. To connect the shapeshifting between the molecular and supramolecular levels, herein, we incorporated the conformational flexibility of star molecules , into the design of giant molecules to develop a shapeshifting molecule that accesses the Ostwald’s stages of nucleation. The design principle was inspired first by Saez and Goodby, who have demonstrated that the gross shapes of star-like molecules can be adjusted by chemically modifying the density and attachment orientation of the peripheral mesogenic groups .…”
Section: Introductionmentioning
confidence: 99%
“…In multicomponent systems, the molar fraction of the constituent components is an essential factor that governs physical properties, physical transitions, and self-assembly of a system . Changes in the molar fractions of the constituent components alter the stabilities of the physical states of a system and result in changes in the self-assembly morphologies. For example, manipulating the molar fraction of the constituent components in block copolymers and giant molecules , has enabled the system to create supramolecular architectures, including 1D nanorods, 2D nanosheets, and 3D interpenetrating networks. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to their use as nano‐building blocks, MNPs such as C 60 and POSS have also been applied as the core units of dendrimers. By attaching peripheral functional units, as shown in Figure , functional materials including amphiphilic MNPs, photoactive MNPs, electroactive MNPs, and bioactive MNPs have been synthesized.…”
Section: Introduction To Dendrimers and Functional Molecular Nanopartmentioning
confidence: 99%